B asked in Science & MathematicsPhysics · 1 decade ago

# A^k matrix singularity and (A^k)^-1 = (A^-1)^k?

Let A be nonsingular. Prove That for any positive integer k , A^k is nonsingular, And (A^k)^-1 = (A^-1)^k.

### 1 Answer

Relevance
• Anonymous
1 decade ago
Favorite Answer

Base case k=1: A^1 = A is non singular -ok-

(Note: the base case could be k=0 if you accepted A^0 = Identity matrix)

Inductive step: assume A^k non singular, prove A^(k+1) is non singular.

A^(k+1) = A^k A is a product of two non singular matrices, so its non singular -ok-. The statement used can be proved using

det(M) = 0 if and only if M is singular,

and det (M N) = det(M) det (N).

So if neither det(M) = 0 nor det(N)=0, then det(MN) is not equal 0, so MN is non singular.

-------

The second proposal can also be demonstrated inductively. But its more intuitive to write out (A^-1)^k A^k and show that the result is the Identity matrix...

(A^-1)(A^-1)...(A^-1) A A ... A = I

As a matter of fact, the first proposition can be showed to be true this way, but is more formal if you use complete induction.

Still have questions? Get your answers by asking now.